PENGEMBANGAN APLIKASI GUI MATLAB UNTUK MENAKSIR KOEFISIEN PARAMETER MODEL REGRESI NON LINIER MENGGUNAKAN ALGORITMA LEVENBERG MARQUARDT - Atika Ratna Dewi (Universitas Pendidikan Ganesha, 2020)
This study aims to make a simple application using the Matlab GUI to estimate parameters in non-linear regression models. The algorithm used in parameter estimation is the Levenberg Marquardt algorithm. The algorithm is written in the MATLAB programming language syntax and is presented in the form of a GUI. The method used in making the application starts from the analysis phase, the interface design stage, the coding stage and the testing phase. The results obtained are the Matlab GUI application that can facilitate the estimation of parameters in the non linear regression model . The parameters chosen are based on the smallest AIC and SC values at t = 0. So the non-linear regression model is obtained, namely . The results of this study can be used as learning media and analytical tools on the subject of parameter assessment in non-linear regression models.